(untitled) (Tanzania Medical Journal, 2022)
Background In Tanzania, cancer of the larynx is second in occurrence among head and neck cancers. Laryngeal cancer is increasing in developing countries and most patients present at advanced stages. Management of laryngeal cancer in developing countries is complicated by the late presentation and lack of health care resources. There is little documented information about the profile of laryngeal cancer patients in Tanzania. This study aimed to determine the clinical-pathological profile and treatment outcome of laryngeal cancer patients treated at the Ocean Road Cancer Institute (ORCI) from 2010 to 2014. Methods This was a retrospective study done at the ORCI by reviewing medical charts of 82 laryngeal cancer patients. Results About half of the patients had a history of smoking and alcohol consumption. The male to female ratio was 10:1 and the mean age at diagnosis was 61 years. Hoarseness of voice was the most common symptom (90.2%) and the mean duration of symptoms was 14.4 months. The majority (73.1%) of the patients had advanced stages. Glottis was the most common site (62.2%). The tracheostomy rate was 75%. The most common (98.8%) histology was squamous cell carcinoma. The most common (60%) primary therapy was radiotherapy alone. Around 84% of the patients were treated with palliative intent with a radiotherapy dose in 2 Gy fractions (EQD2) of less than 60 Gy and the majority (60%) of patients (60%) received only radiotherapy without concurrent cisplatin. The mean EQD2 was 46 Gy for the whole cohort. The mean duration of treatment waiting time was 55.7 ± 72 days for the whole cohort. The mean duration of radiotherapy was 32.8 ± 19.8 days and the mean duration of treatment interruption was 7.4 ± 15 days. Only 13% of the patients were treated with radical concurrent chemo-radiation. None of the patients were treated by either upfront or salvage surgery. The 5 years the overall survival rate (OS) was 26%. Conclusion Laryngeal cancer is more common among elderly males than females in Tanzania. The majority of patients had advanced stages and were treated with low radiotherapy doses without concurrent chemotherapy. The 5 years OS rate was 26%.